Comparative study on telescope differential amplifier and folded-cascode Operational Transconductance (OTA) design using 50nm BSIM4 technology : article / Muhamad Aiman Aisar Mohd Amin - Mohd Amin, Muhamad Aiman Aisar (2012)
This paper presents the comparison between telescopic differential amplifier and folded-cascode OTA design using 50nm BSIM4 Technology. The objective of this project is to compare the parameters of gain and power dissipation between these two design models. Implementation has been done in 50nm BSIM4 technology using LTSpice simulation tools, and use 1.0V voltage supply. The telescopic differential op-amp has gain of 70.5dB and power dissipation of 23.92mV. The folded-cascode OTA has 52dB of gain and 60.8mV of power dissipation. From the simulation results, the Telescopic structure is better in gain and power dissipation than folded-cascode structure.